Relating spatial ability to cognitive style preferences : perception, processing and hemisphericity among low achieving students - Yeo, Alan Kong Leong. (2008)
A recent review of previous studies on cognitive style preferences among students has shown strong relationships between a student's learning style and hemispheric mode preference. This study aims to extend this pool of research by exploring the role of another cognitive variable, spatial visualization. Battista (1992) noted that spatial visualization correlates highly with achievement (r = .30 to .60). This study attempts to answer the following questions: (1) Do subjects with High, Average, and Low spatial visualization ability differ in their preferred learning modes (Concrete Experience, Abstract Conceptualization, Reflective Observation, and Active Experimentation)? (2) Do these three groups of spatial visualization ability differ in their perception and processing dimensions? (3) Do these three groups differ in their preferred learning styles (Assimilator, Converger, Accommodator, and Diverger)? (4) What is the relationship between spatial visualization and brain hemisphericity (left, whole, and right brain dominance)? and (5) What is the relationship between learning styles and brain hemisphericity?